Pornography, sexual violence and crime statistics: a cross-cultural perspective - Landripet, Ivan (Array, 2006)
Objectives. The study tests a theoretical hypothesis, mainly advocated by conservative lawmakers and some of the most prominent feminist authors/activists, according to which pornography use incites men to commit acts of sexual violence. Unlike the majority of empirical efforts aimed at determining relation between pornography use and sexual violence, which are experimental in nature, this study was based upon analyses of the relevant secondary data, the public crime statistics. Taking into account all the limitations of using the particular approach as a sole research method, the aim is also to shed light heuristically on the nature of sexual violence. Design and methods. According to one of the socially most concerning implications of the hypothesis, the increase in porn availability will significantly contribute to the increase in sexual crime (moreover, it should inevitably cause it to soar). The authors have therefore analyzed relevant crime statistics (rape and sexual assault) of the past several decades for the United States, Japan and Croatia, in order to determine temporal dynamics of sexual crime during a time span sufficiently long to cover transition from pornographic scarcity to abundance of easily available sexually explicit material in each country. Those trends were controlled for the dynamics of comparable non-sexual crime (murder and assault) during the same period. Results. Both sexual and non-sexual crimes manifest evidently corresponding dynamics in each national study. During most of the respective period, the incidence of both types of crime is consistently rising in the United States, declining in Japan, and fluctuating in Croatia. Controlled also for the potential intervening factors, such as changes in law, methodology of keeping crime statistics and trends of prosecuting the reported sexual offenses, the results do not indicate independent increase in sexual crime conditioned by the increase in porn availability. Conclusion. The authors reject the thesis using three national case studies, deliberately involving societies that are culturally, historically and demographically very distinct. In terms of identifying the nature of rape and other forms of sexual coercion, it rather seems plausible to support certain "macroscopic" interpretations. The two types of violent crimes may either be determined by structural causes (such as social disorganization, gender inequality – sexism, violent nature of society in general, etc.), or share identical, violent nature (sexual violence is primarily an act of physical violence, and only secondly a sexual act). To a certain degree, the results even corroborate the theory of pornographic substitution, according to which consumption of (violent) pornography may provide a surrogate for violent sexual behavior.